Dose conversion coefficients for Chinese reference adult male and female voxel phantoms from idealized neutron exposures. Issue 9 (2nd September 2017) - Liu, Huan; Li, Junli; Qiu, Rui; Wu, Zhen; Pan, Yuxi; Li, Chunyan
ABSTRACT: A whole-body voxel phantom called CRAF representing the Chinese adult female was constructed in this study from color photographs. The CRAF has a height of 160 cm and a weight of 54 kg with 80 organs and tissues, including almost all organs required in the ICRP Publication 103. Masses of all organs in CRAF are consistent with the Chinese reference data within 1%. Our research group has previously developed a Chinese reference adult male phantom called CRAM, which has a height of 170 cm and a weight of 60 kg with 80 tissues and organs. A new set of fluence-to-dose conversion coefficients based on the Chinese reference adult voxel phantoms CRAM and CRAF are presented for six idealized external neutron exposures from 10 −8 MeV to 20 MeV. The calculation of organ-absorbed doses and effective doses were performed with the Monte Carlo transport code MCNPX 2.4. The resulting dose conversion coefficients were compared with those published in ICRP Publication 116, which represents the reference Caucasian. It was observed that the two sets of organ-absorbed dose conversion coefficients agreed well for most organs in ROT and ISO geometry; however, considerable deviations were found in some organs in AP, PA, RLAT and LLAT exposures. Organ-absorbed dose coefficients difference showed good agreement with the difference of organ depth distribution between Chinese and ICRP phantoms. For neutrons with energies above 2 MeV, the effective dose conversion coefficients of Chinese reference adult are almost identical to those of ICRP Publication 116 in AP, PA, ROT and ISO geometries, while are generally 15% higher than those of ICRP Publication 116 from lateral geometries. When energies range from 10 −8 MeV to 1 MeV, differences are within 10% in AP (–5%), PA (–8%) and ROT (4%) geometries; however, relatively large discrepancies are shown in lateral and ISO geometries, with differences of 15% for LLAT, 20% for RLAT and 12% for ISO, respectively.